2020
DOI: 10.1108/f-03-2020-0022
|View full text |Cite
|
Sign up to set email alerts
|

The experience of patients in an outpatient infusion facility: a qualitative study

Abstract: Purpose As hospitals are now being designed with an increasing number of single rooms or cubicles, the individual preference of patients with respect to social contact is of great interest. The purpose of this study is to gain a better understanding of the experience of patients in an outpatient infusion center. Design/methodology/approach A total of 29 semi-structured interviews were conducted, transcribed and analyzed by using direct content analysis. Findings Findings showed that patients perceived a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…While the curtains in the recovery area provided an enclosure, they did not provide auditory and visual privacy for patients and their parents while communicating about sensitive health information. Importance of privacy within healthcare settings has also been discussed in previous studies (Peditto et al, 2020;Zijlstra et al, 2020), and an enclosed private recovery area could address the privacy needs of the patients.…”
Section: Discussionmentioning
confidence: 98%
“…While the curtains in the recovery area provided an enclosure, they did not provide auditory and visual privacy for patients and their parents while communicating about sensitive health information. Importance of privacy within healthcare settings has also been discussed in previous studies (Peditto et al, 2020;Zijlstra et al, 2020), and an enclosed private recovery area could address the privacy needs of the patients.…”
Section: Discussionmentioning
confidence: 98%
“…The lack of significance can be explained because patients in this study received infusion therapy with corresponding alarms of infusion pumps. In a previous qualitative study, patients explained they could not sleep due to these alarms, regardless of whether they had roommates or not (Zijlstra et al , 2020). Results showed significant effects of the explanatory variables age, sleep medication and global health.…”
Section: Discussionmentioning
confidence: 99%
“…The primary investigation of literature led to the realization that wayfinding wa En and bin Bebit [128] conducted a study focused on analyzing reactions to signage design within a healthcare facility, whereby a qualitative approach by adopting an interview was suggested as an examination technique. Moreover, a study conducted by Zijlstra et al [129] focused on simulated physical ageing indicated that rout complexity can affect aging people negatively when a wayfinding experiment was conducted to simulate the elderly. Other Studies have focused on the effect of cognitive impairments such as dementia and Alzheimer's on wayfinding performance in healthcare facilities [9].…”
Section: Conceptual Framework For the Assessment Of Wayfinding Perfor...mentioning
confidence: 99%